Targeting the annexin 1‐formyl peptide receptor 2/ALX pathway affords protection against bacterial LPS‐induced pathologic changes in the murine adrenal cortex. Issue 7 (27th March 2015) - Buss, Nicholas A. P. S.; Gavins, Felicity N. E.; Cover, Patricia O.; Terron, Andrea; Buckingham, Julia C.
ABSTRACT: Hypothalamo‐pituitary‐adrenocortical dysfunction contributes to morbidity and mortality in a high proportion of patients with sepsis. Here, we provide new insights into the underlying adrenal pathology. Using a murine model of endotoxemia (LPS injection), we demonstrate that adrenal insufficiency is triggered early in the disease. LPS induced a local inflammatory response in the adrenal gland within 4 hours of administration, coupled with increased expression of mRNAs for annexin A1 (AnxA1) and the formyl peptide receptors [(Fprs) 1, 2, and 3], a loss of lipid droplets in cortical cells (index of availability of cholesterol, the substrate for steroidogenesis), and a failure to mount a steroidogenic response to ACTH. Deletion of AnxA1 or Fpr2/3 in mice prevented lipid droplet loss, but not leukocyte infiltration. LPS increased adrenal myeloid differentiation primary response gene 88 and TLR2 mRNA expression, but not lymphocyte antigen 96 or TLR4. By contrast, neutrophil depletion prevented leukocyte infiltration and increased AnxA1, Fpr1, and Fpr3 mRNAs but had no impact on lipid droplet loss. Our novel data demonstrate that AnxA1 and Fpr2 have a critical role in the manifestation of adrenal insufficiency in this model, through regulation of cholesterol ester storage, suggesting that pharmacologic interventions targeting the AnxA1/FPR/ALX pathway may provide a new approach for the maintenance of adrenal steroidogenesis in sepsis.—Buss, N. A. P. S., Gavins, F. N. E., Cover, P. O., Terron, A., Buckingham, J. C. Targeting the annexin 1‐formyl peptide receptor 2/ALX pathway affords protection against bacterial LPS‐induced pathologic changes in the murine adrenal cortex. FASEB J . 29, 2930‐2942 (2015). www.fasebj.org